Background and motives for the conference - Jaworski, Barbara; Kleve, Bodil (NOMAD Nordic Studies in Mathematics Education, 2000)
The theme of this conference, which was held in Gausdal in March 2000, was Social Constructivism, Social Practice Theory and Sociocultural Theory: Relevance and Rationalisations in Mathematics Education. Jaworski (this issue) writes: "These are theories that are in the public domain; that have been discussed by scholars, argued over, rationalised; terms have evolved and, in each case, a discourse has emerged which itself conditions thinking and communication".